Association of liver injury from specific drugs, or groups of drugs, with polymorphisms in HLA and other genes in a genome-wide association study - Nicoletti, Paola; Aithal, Guruprasad P.; Bjornsson, Einar S.; Andrade, Raul J.; Sawle, Ashley; Arrese, Marco; Barnhart, Huiman X.; Bondon-Guitton, Emmanuelle; Hayashi, Paul H.; Bessone, Fernando; Carvajal, Alfonso; Cascorbi, Ingolf; et al. (WB Saunders, 2016)
Background & aims: We performed a genome-wide association study (GWAS) to identify genetic risk factors for drug-induced liver injury (DILI) from licensed drugs without previously reported genetic risk factors. Methods: We performed a GWAS of 862 persons with DILI and 10588 population-matched controls. The first set of cases was recruited prior to May 2009 in Europe (n=137) or the USA (n=274). The second set of cases were identified from May 2009 through May 2013 from international collaborative studies performed in Europe, the USA and South America. For the GWAS, we included only cases of European ancestry associated with a particular drug (but not flucloxacillin or amoxicillin-clavulanate). We used DNA samples from all subjects to analyze human leukocyte antigen (HLA) genes and single nucleotide polymorphisms (SNPs). After the discovery analysis was concluded, we validated our findings using data from 283 European patients with diagnosis of DILI associated with various drugs. Results: We associated DILI with rs114577328 (a proxy for A*33:01 a HLA class I allele; odds ratio [OR], 2.7; 95% CI, 1.9–3.8; P=2.4x10–8) and with rs72631567 on chromosome 2 (OR, 2.0; 95% CI, 1.6–2.5; P=9.7x10–9). The association with A*33:01 was mediated by large effects for terbinafine-, fenofibrate-, and ticlopidinerelated DILI. The variant on chromosome 2 was associated with DILI from a variety of drugs. Further phenotypic analysis indicated that the association between DILI and A*33:01 was significant, genome wide, for cholestatic and mixed DILI, but not for hepatocellular DILI; the polymorphism on chromosome 2 associated with cholestatic and mixed DILI as well as hepatocellular DILI. We identified an association between rs28521457 (within the LRBA gene) and only hepatocellular DILI (OR, 2.1; 95% CI, 1.6–2.7; P=4.8x10–9). We did not associate any specific drug classes with genetic polymorphisms, except for statin-associated DILI, which was associated with rs116561224 on chromosome 18 (OR=5.4; 95% CI, 3.0–9.5; P=7.1x10–9). We validated the association between A*33:01 terbinafine- and sertraline-induced DILI. We could not validate the association between DILI and rs72631567, rs28521457, or rs116561224 Conclusions: In a GWAS of persons of European descent with DILI, we associated HLA-A*33:01 with DILI due to terbinafine and possibly fenofibrate and ticlopidine. We identified polymorphisms that appear to be associated with DILI from statins, as well as 2 non–drug-specific risk factors.